Depressive symptoms, inflammation, and ischemic stroke in older adults: a prospective analysis in the cardiovascular health study. - Arbelaez, Jose J; Ariyo, Abraham A; Crum, Rosa M; Fried, Linda P; Ford, Daniel E (J Am Geriatr Soc, 2007)
OBJECTIVES: To investigate the mediator role of inflammation in any relationship between depressive symptoms and ischemic stroke. DESIGN: Longitudinal prospective study. SETTING: Review of medical records, death certificates, and the Medicare healthcare utilization database for hospitalizations. PARTICIPANTS: Total of 5,525 elderly men and women aged 65 and older who were prospectively followed from 1989 to 2000 as participants in the Cardiovascular Health Study. MEASUREMENTS: Depression symptom scores, inflammatory markers. RESULTS: Greater depressive symptoms were associated with risk of ischemic stroke (unadjusted hazard ratio (HR)=1.32, 95% confidence interval (CI)=1.09-1.59; HR=1.26, 95% CI=1.03-1.54, adjusted for traditional risk factors). When a term for inflammation (C-reactive protein (CRP)) was introduced in the model, the HRs were not appreciably altered (unadjusted HR=1.31, 95% CI=1.08-1.58; adjusted HR=1.25, 95% CI=1.02-1.53), indicating that CRP at baseline was not a mediator in this relationship. In analyses stratified according to CRP levels, a J-shaped relationship between depressive symptoms and stroke was evident in the unadjusted analyses; in the fully adjusted model, only CRP in the highest tertile was associated with a higher risk for stroke in the presence of higher depressive symptoms scores. CONCLUSION: The analyses from this prospective study provide evidence of a positive association between depressive symptoms and risk of incident stroke. Inflammation, as measured according to CRP at baseline, did not appear to mediate the relationship between depressive symptoms and stroke.
Keywords: Aged; C-Reactive Protein; Cardiovascular Diseases; Cerebral Infarction; Cohort Studies; Depression; Female; Geriatric Assessment; Humans; Inflammation; Kaplan-Meier Estimate; Longitudinal Studies; Male; Multivariate Analysis; Personality Assessment; Proportional Hazards Models; Prospective Studies; Psychoneuroimmunology; Risk Factors; Socioeconomic Factors; Statistics as Topic; United States